Estrogen maintains mitochondrial content and function in the right ventricle of rats with pulmonary hypertension. Issue 6 (21st March 2017) - Liu, Aiping; Philip, Jennifer; Vinnakota, Kalyan C.; Van den Bergh, Francoise; Tabima, Diana M.; Hacker, Timothy; Beard, Daniel A.; Chesler, Naomi C.
Abstract: The typical cause of death in pulmonary hypertension (PH) is right ventricular (RV) failure, with females showing better survival rates than males. Recently, metabolic shift and mitochondrial dysfunction have been demonstrated in RV failure secondary to PH. In light of evidence showing that estrogen protects mitochondrial function and biogenesis in noncardiovascular systems, we hypothesized that the mechanism by which estrogen preserves RV function is via protection of mitochondrial content and oxidative capacity in PH. We used a well‐established model of PH (Sugen+Hypoxia) in ovariectomized female rats with/without estrogen treatment. RV functional measures were derived from pressure–volume relationships measured via RV catheterization in live rats. Citrate synthase activity, a marker of mitochondrial density, was measured in both RV and LV tissues. Respiratory capacity of mitochondria isolated from RV was measured using oxygraphy. We found that RV ventricular‐vascular coupling efficiency decreased in the placebo‐treated SuHx rats (0.78 ± 0.10 vs. 1.50 ± 0.13 in control, P < 0.05), whereas estrogen restored it. Mitochondrial density decreased in placebo‐treated SuHx rats (0.12 ± 0.01 vs. 0.15 ± 0.01 U citrate synthase/mg in control, P < 0.05), and estrogen attenuated the decrease. Mitochondrial quality and oxidative capacity tended to be lower in placebo‐treated SuHx rats only. The changes in mitochondrial biogenesis and function paralleled the expression levels of PGC‐1 α in RV. Our results suggest that estrogen protects RV function by preserving mitochondrial content and oxidative capacity. This provides a mechanism by which estrogen provides protection in female PH patients and paves the way to develop estrogen and its targets as a novel RV‐specific therapy for PH. Abstract : Motivated by the clinical observation that female patients have superior right ventricular (RV) functional adaption in pulmonary hypertension (PH), we investigated the metabolic mechanisms by which estrogen offers protection to RV function in a rat model of PH. Our study for the first time reveals that estrogen preserves RV mitochondrial density and tends to preserve function in PH‐induced RV hypertrophy, which may underlie the estrogenic improvement of RV contractility and mechanical efficiency. We believe that our findings will contribute to an improved understanding of RV failure and more effective therapies to combat this devastating disease.